(untitled) (Research, Society and Development, 2020)
Learning Styles are individual preferences in the learning process. The objective of the study is to verify if there is a predominance of some learning style in students of the Physical Education course, and if there is a relationship between the styles with the sex and period they were enrolled. For this, the questionnaire Learning Styles Index (New Index of Learning Styles - N-ILS) was applied, in the months of November and December 2019, to 73 university students of the physical education course, of a higher education institution, located in the Zona da Mata Mineira. The data were analyzed using descriptive statistics (mean, standard deviation and frequency measures). Pearson’s chi-square test (X2) was used, adopting a significance level of 5%, to verify associations with sex and the period they were enrolled in. It was identified that the majority are enrolled in the 6th (47.9%) and 8th (28.8%) period, they are male (50.7%). They have active (63.0%), sensory (82.2%), verbal (52.1%) and sequential (79.5%) learning poles. No differences were identified between the dimensions and poles of the learning styles, as to the sex and period they were enrolled in. However, it was identified that in the perception dimension, the sensory pole, and in the understanding dimension, the sequential pole, are predominant in the sixth and eighth period of the course. We conclude that it is essential to know the learning styles of the students in order to promote a balance with the teaching practices adopted by the teachers.